CDNA CLONING AND HETEROLOGOUS EXPRESSION OF AN ENDO‐β‐1, 4‐GLUCANASE FROM THE FUNGUS‐GROWING TERMITE Macrotermes barneyi. Issue 3 (9th April 2014) - Ni, Jinfeng; Wu, Yan; Yun, Chao; Yu, Menglan; Shen, Yulong
<x xml:space="preserve">Abstract</x> Major β‐glucosidase (BG) and endo‐β‐1, 4‐glucanase (EG) activities were localized to the midgut of the fungus‐growing termite Macrotermes barneyi. Previously, we obtained the endogenous BG gene (MbmgBG1) from the midgut of M. barneyi. Here, we report the cDNA cloning of another endogenous cellulase, the EG protein MbEG1. This cellulase was partially purified from crude extract of the midgut of worker termites using zymogram analysis. Based on the N‐terminal amino acid sequence and using rapid amplification of cDNA ends (RACE), a full‐length cDNA of 1, 843 base pairs was obtained. This encoded 448 amino acids and the sequence was similar to that of the members of glycoside hydrolase family 9. The MbEG1 transcript was detected primarily in the midgut using quantitative real‐time polymerase chain reaction (PCR). To confirm functional activity of MbEG1, heterologous expression was conducted in both Escherichia coli and Pichia pastoris expression systems. Results indicated that MbEG1 could be functionally expressed in P. pastoris. This study provides the information that may facilitate understanding of cellulolytic systems in fungus‐growing termites.